DIGITAL TRANSFORMATION OF FOOD PRODUCTION IN EUROPE AND OPPORTUNITIES FOR ITS ADAPTATION IN BULGARIA - G. Aleksiev (Trakia Journal of Sciences)
Agricultural production in Europe has been focused on increasing its efficiency and improving its ecological imprint. New digital technologies have created opportunities to achieve these goals and thus created a competition among producers for their implementation on a large scale. In the meantime, CAP of EU has presented multiple forms of support for the digital transformation of the sector. The goal of this study is to analyze the key points of digital transformation of agricultural production in Europe and distinguish the opportunities for technological adaptation of digital solutions in Bulgaria. In order to achieve this goal the following tasks must be solved: to analyze the means of digital transformation of food production in Europe and its main advantages; to recognize the opportunities for transfer of technologies and solutions adapted for the Bulgarian agricultural sector.